IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK KELAS IX DI MTs. NU SUNAN GIRI PRIGEN PASURUAN - Syaikhudin, M (UII Darullughah Waddawah Pasuruan, 2022)
The problem in this study is to determine the implementation of akidah akhlak learning in the formation of the religious character of students in class IX Mts. Nu Sunan Giri Prigen Pasuruan, supporting and inhibiting factors as well as the results of the implementation of Akidah Akhlak learning in the formation of the religious character of class IX Mts. Nu Sunan Giri Prigen Pasuruan. This research was conducted at IX Mts. Nu Sunan Giri Prigen Pasuruan. Research subjects and informants were class IX class teachers of morals and eighth- grade students. The method used in this research is descriptive qualitative, which is in the form of written or oral data from the research object at the institution. Data were collected using observation, interview, and documentation techniques. Meanwhile, data analysis used Miles and Huberman's data analysis techniques, namely data reduction, data modeling (data display), and drawing conclusions. The results of the study concluded that the implementation of akidah akhlak subjects in the formation of the religious character of grade IX Mts. Nu Sunan Giri Prigen Pasuruan used exemplary and habituation methods such as praying before learning begin, praying in congregation, following the Quran Tahsinul program, accustoming praiseworthy behavior, and respecting teachers. and friends. This is in order to support the values of the students' religious character which will be applied in everyday life and become an example. The inhibiting factors: Insufficient time allocation and and the behavior of students.